Market Structure and Price Transmission of Eggs Commodity - Ahmad, Abdul Aziz; Arifin, Agus; Chew, Boon Cheong (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
Purposes of this research are to determine some characteristics of distribution channel, market structure, and price maker transmission in purebred chicken egg commodity in Banyumas District, Central Java Province. Primary data applied on this research is from all channel distribution levels; from producers to final consumers. Meanwhile secondary data is collected from government official sources, such as BPS-Statistic of Banyumas Disrict, Banyumas Department of Industry, Trading and Cooperation, and previous researches which has been made by researcher team. Sample determining is directed by proportional random sampling methods. Some measurements are applied to this research, including to; Herfindahl Index (HI), Concentration Ratio (CF), and Minimum Efficiency Scale (MES) to investigate market structure; and Asymmetric Price Transmission (APT) to determine price transmission mechanism model. This research finds that (1) the distribution channel of egg commodity is spitted to different channel, the first channel: egg producer â retail traders â final consumers, and second channel: egg producers â whole seller â retail traders â final consumers; (2) market structure which is created to this farming specific commodity is perfect market; (3) price transmission mechanism analysis statistically shows that there is almost no existence of dominant power in price formation.